7 princípios do cooperativismo: uma proposta de medição da percepção dos associados - Lutz, Sérgio (Universidade do Vale do Rio dos Sinos, 2021)
Cooperativism seeks to transform the world into a fairer, more balanced place with better opportunities for all. In order to achieve its objective, it relies on values and principles. In this context, the starting point for this work was a reflection on the real knowledge that members have about the universal principles of Cooperativism. The objective was to create a tool that would make it enable assessing the perception of members regarding the application of the 7 principles of Cooperativism. A questionnaire was proposed and developed to achieve this goal using the Design Science Research method. The questionnaire was built with the participation of specialists in the Cooperatives field; it was tested through pre-tests and, subsequently, applied to members. Five branches of cooperatives participated in the research: Credit, Health, Transport, Labor, Production of Goods and Services and Agriculture. A total of 442 cooperative members from the states of Rio Grande do Sul, Santa Catarina, Paraná and São Paulo answered the questionnaire. The survey was made available through email and Whatsapp messages sent to respondents. After data collection the questionnaire was tested using the SPSS Statistics software, and the validation of the constructs was performed through Factor Analysis and the measurement of reliability by Cronbach's Alpha indicator. After testing the results, 3 variables were excluded, and 25 respondents’ answers were removed as they were considered outliers. The final format of the questionnaire involved 46 questions that made it possible to deal satisfactorily with the 7 principles of Cooperativism. As a result, one can verify the effectiveness of the questionnaire. In addition to external variables such as age and gender, among others, the perceptions of members regarding the application of the principles in their cooperative were collected using a Lickert scale of 8 points (from 0 - I totally disagree to 7 - I totally agree). As an illustration of the potential use of the questionnaire, the data allowed comparing the averages of the principles among themselves distributed according to the branches that participated in the research and to relate to possible decision-making process based on the results. It was also possible to calculate the level of satisfaction of members about the cooperative through the use of the Net Promoter Score technique. For this collection, an 11-point Lickert scale (0 to 10) was used.
Keywords: Cooperativismo; Educação cooperativa; Princípios do cooperativismo; Percepção do associado de cooperativa; Índice de satisfação do associado de cooperativa; Cooperative education; Cooperative; Cooperative principles; Perception of the cooperative member; Cooperative member satisfaction index; ACCNPQ::Ciências Sociais Aplicadas::Administração